Integrated Socio Epidemiological Model for Leptospirosis Control in Tidal Flood Prone Areas - Risna Endah Budiati; Suharyo Hadisaputro; Mateus Sakundarno Adi; Rr. Anggun Paramita Djati; Suhartono; Tri Ramadhani (Jurnal Kesehatan Masyarakat, 2026)
The Elderly populations in tidal flood-prone areas face heightened vulnerability to leptospirosis due to environmental hazards, recurrent inundations, and psychosocial stressors. This study analyzed an integrated socio-epidemiological model that accommodates a community-based intervention, targeting perceived stress, self-efficacy, and clean and healthy living behavior (PHBS), along with a system dynamics simulation to forecast leptospirosis incidence. This quasi-experimental study design was implemented with 70 participants (35 intervention and 35 control). The participants reside in flood-affected villages of Demak Regency, Indonesia, in 2024 (Purwosari, Sriwulan). Perceived stress (PSS-10), self-efficacy, and PHBS scores were measured at pre- and postintervention. Statistical analyses included Mann-Whitney, Wilcoxon, and paired t-tests. Delta scores were integrated into a stock-flow model (PowerSim Studio 10) incorporating behavioral and environmental risk variables to simulate leptospirosis cases for 2024–2029. The in- tervention group demonstrated significant improvements in self-efficacy (Δ=+5.69±8.17,p<0.001) and PHBS (Δ=+9.37±4.59, p<0.001), alongside a non-significant but clinically relevant reduction in perceived stress (Δ=-7.20±8.33, p=0.733 vs control). The dynamic model projected a 25–30% reduction in leptospirosis cases over five years with intervention, compared to a ≤5% decline without behavioral programs. Visual validation indicated alignment between simulated and real incidence trends (2020–2024). Integrating psychosocial behavioral interventions with dynamic modeling provides a reliable framework for leptospirosis control in flood-prone populations.